Perlindungan Hukum Bagi Pemegang Hak Cipta Atas Lagu yang didownload di Internet = Legal Protection for the Holder of Copyright on Songs Down - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research aimed to understand the factors inhibiting legal protection for song creators from free internet-downloading and, causes for difficulties in punishing downloading songs from internet. It conducted field research, and library research for support. Considering its narrow scope of research location and respondents, the research applied qualitative analysis after data classification according to certain topics. The research results show the followings: 1. The factors inhibiting legal protection, for song creators from free internet downloading include: a. Creators' lack of understanding on their own economic rights. b. Lack of appreciation from the society for the work of song creators, resulting in free internet downloading. 2. The dispute resolution faces difficulties in deciding the punishment, for free song downloading from internet, since the police have no accurate understanding on the Act no 19/2002 concerning copyrights. In addi-tion, the creators must be more active to file their complaints, despite the fact that the infringement of song copyrights is categorized as ordinary delict in the Act no 19/2002, whenever they find out that their songs are offered for free download without their written permission. Song creators must play more active role as they are supposed to know better the origi-nality of their creation.